Seaweed Community and Succession on a Trapezoidal-Shaped Artificial Reef - Jung, Seung Wook; Choi, Chang Geun (Ocean science journal, 2022)
This study conducted a community and succession analysis of an artificial reef and natural rock mass near the eastern coast of Guryongpo-eup, Pohang-si, from November 2016 to August 2018. A total of 130 species of macroalgae were identified during the study period, which included 85 species in artificial reefs and 110 species in natural rock masses (~ 1 km apart). The average biomass of macroalgae on the two locations was 1,110.89 g/m 2 , ranging from 312.63 to 1,909.72 g/m 2 , depending on the survey period. Upon analyzing the ecological indices for each station at different survey periods, our findings indicated that the species richness, evenness, diversity, and dominance indices for the artificial reefs ranged from 2.13 to 8.14, 0.17 to 0.48, 0.62 to 1.63, and 0.24 to 0.70, respectively, whereas those for natural rock masses ranged from 1.61 to 10.44, 0.07 to 0.58, 0.19 to 1.90, and 0.21 to 0.92. The analysis of the succession of macroalgal communities for 2 years after the initial installation of the artificial reef indicated that the second survey showed the highest species composition, and the third survey showed a marked decline. Species-level biomass analysis during the survey period revealed that the biomass of the artificial reef steadily increased over the 2-year survey due to the succession from a dominant community of Colpomenia sinuosa , an opportunistic species (6 months after the reef installation): a dominant community of Gelidium elegans , perennial red alga (9–18 months later) and a dominant community of Ecklonia cava , a perennial brown algae (continued after 21 months). These results indicate that the macroalgae community of the artificial reef showed a species composition and a community structure similar to that of natural rock masses. Therefore, our results highlight the importance of characterizing the dominant species and life cycle of macroalgae in a target region prior to the establishment of artificial reef, as it provides critical insights into their attachment behavior, species composition, and succession patterns.